2018
DOI: 10.1590/1678-4324-2018160526
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Assessment of a Poly(methyl methacrylate) Synthesized for the Direct Fabrication of Bone Tissues

Abstract: A cytotoxicity study is performed on a poly(methyl methacrylate) polymer (PMMA) to be used for the fabrication of bone tissue by Rapid Prototyping (RP). The solution polymerization is conducted in a pilot plant reactor using more appropriated reagents in consideration of the medical application. Moreover, the polymer is efficiently handled to avoid the side effect of the monomer, reducing the concentration of this specie to 287,731 µg MMA/kg PMMA. The cytotoxicity of the polymer is determined through growth mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…Therefore, both qualitative and quantitative cytotoxicity tests carried out in direct and indirect contact with L929 cells suggested that the investigated samples (PMMA/ZnO NPs and PMMA) did not cause cytotoxicity. The absence of cytotoxicity of our samples of PMMA is in accordance with published results [41]. In contrast, ZnO NPs are cytotoxic [19,20,42].…”
Section: Cytotoxicitysupporting
confidence: 93%
“…Therefore, both qualitative and quantitative cytotoxicity tests carried out in direct and indirect contact with L929 cells suggested that the investigated samples (PMMA/ZnO NPs and PMMA) did not cause cytotoxicity. The absence of cytotoxicity of our samples of PMMA is in accordance with published results [41]. In contrast, ZnO NPs are cytotoxic [19,20,42].…”
Section: Cytotoxicitysupporting
confidence: 93%
“…The results obtained in this assay shows an intense red fluorescence for positive toxicity control confirming the death of the cells present for both cell lines, and an intense and similar green fluorescence for negative toxicity control and for the cells that were in contact with the membranes (PLLA). These results can be compared with literature [17], where the results for 24 hours of contact of the cells in controls and in contact with material have a similar behavior. In both cases, the materials and the negative controls are intense green colored indicating live cells and the positive controls are red colored what indicates cell death.…”
Section: Discussionsupporting
confidence: 53%
“…Nevertheless, it was found that the photopolymers were highly toxic due to the presence of UFP, nano-sized particles less than 100 nm in diameter, known to be released from ABS materials. PMMA biocompatibility has been proven by results of a recent 72 h cytotoxicity assessment of samples, as determined through growth monitoring, adherence, and morphology of L-929 cells in which a similar ethanol-based protocol was used for sterilization [ 119 ]. However, the above-mentioned samples were not photopolymerized, unlike the custom-printed SLA-fabricated piece in the current study.…”
Section: Discussionmentioning
confidence: 99%